The contribution of digitized electroencephalogram in the clinical and therapeutic monitoring of substance uses disorders - Mengad, Aziz; Ertel, Merouane; Chakkouch, Meryem; Ouaamr, Ahmed; Elomari, Fatima (Institute of Advanced Engineering and Science, 2024)
The approaches used in clinical and therapeutic monitoring in addictology are multiple and generally based on subjective instruments such as interviews or observations. However, the lack of frankness can be an obstacle, as the patients monitored may not be entirely honest in their responses, and improvement in symptoms does not always mean continued abstinence. This article proposes a new objective method for monitoring the clinical and therapeutic evolution of addicted patients based on the study of electro-physiological changes collected by digitized electroencephalogram (EEG). The study is a case-control study of 30 hospitalized addicts who met the diagnostic and statistical manual of mental disorders (DSM-V) criteria for substance use disorders substance use disorders (SUD) and who underwent a standard digitized EEG at the end of their hospitalization. A control group of 30 healthy individuals was also included. This research shows a dominance of rapid-frequency beta 2 and hypovolted alpha 2 rhythms in cases with a clear sensitivity to activating maneuvers occasioned by hyperpnoea (HPN) and intermittent light stimulation (ISL) giving either a significant slowing of electrogenesis, bi-occipital entrainment, or an oculo-clonic response signifying a need for further care. However, the major challenge in understanding the EEG signal is that it is not always specific to SUD and suggests the need to consider the trans-diagnostic framework.